Development of problem-based learning module in economics to increase students’ critical thinking - Lailatul Maghfiroh; Endang Mulyani (Universitas Pendidikan Ganesha, 2019)
Module is a teaching material as an important component in the learning process. This research aims to produce economic learning modules with a problem based learning approach for students of class XI IPS that are feasible and effective to improve critical thinking skills. This type of research is research and development developed by Borg and Gall with the following stages: (1) preliminary study, (2) planning, (3) initial product development, (4) initial field test, (5) revision of main products, (6) test of main products, (7) revision of operational products, (8) test of operational fields, (9) revision of final products, (10) distribution. The economic learning module with the problem based learning approach was tested in the control and experimental classes, each of the 35 X-IPS students in MAN 2 Jombang. The result of research are: 1) Economic Learning Modules with Problem Based Learning Approaches which is feasible based on the material and media experts in the category of